2022
DOI: 10.3390/ijms232012348
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Proliferative and Apoptotic Effects of Hydroxytyrosyl Oleate on SH-SY5Y Human Neuroblastoma Cells

Abstract: The antitumor activity of polyphenols derived from extra virgin olive oil and, in particular the biological activity of HTyr, has been studied extensively. However, the use of HTyr as a therapeutic agent for clinical applications is limited by its low bioavailability and rapid excretion in humans. To overcome these limitations, several synthetic strategies have been optimized to prepare lipophenols and new compounds derived from HTyr to increase lipophilicity and bioavailability. One very promising ester is hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…HTyr is the main phenol present in EVOO. It is a small, catecholic compound exhibiting antioxidant, cardioprotective, anticancer, neuroprotective and anti-inflammatory activities [ 42 , 43 , 44 , 45 , 46 , 47 ]. Because of these interesting properties, it has a high therapeutic potential and is used as a supplement and preservative for cosmeceutical, nutraceutical and food applications.…”
Section: Hydroxytyrosol (Htyr)mentioning
confidence: 99%
“…HTyr is the main phenol present in EVOO. It is a small, catecholic compound exhibiting antioxidant, cardioprotective, anticancer, neuroprotective and anti-inflammatory activities [ 42 , 43 , 44 , 45 , 46 , 47 ]. Because of these interesting properties, it has a high therapeutic potential and is used as a supplement and preservative for cosmeceutical, nutraceutical and food applications.…”
Section: Hydroxytyrosol (Htyr)mentioning
confidence: 99%
“…The main phenolic components of VOO are the secoiridoid derivatives of hydroxytyrosol (HTy) and tyrosol (Ty), with the hydroxytyrosol-containing phenolic components having the highest biological activities. They are the most effective in preventing chronic diseases due to their superior ability to reduce chronic inflammation and oxidative damage and their potent anti-proliferative activity [ 3 , 4 ]. In this sense, scientific evidence on the health benefits of HTy has led the European Food Safety Authority (EFSA) to approve a health claim that states “olive oil polyphenols contribute to the protection of blood lipids from oxidative stress”.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors tested HTyr-rich extracts from olive oil mill wastewater, demonstrating that the extracts exhibit antiproliferative and pro-apoptotic effects on the human HL60 cancer cell line and avoids toxicity in the non-tumor cell line [ 106 ]. A recent study confirmed the induction of apoptotic and antiproliferative activity on SH-SY5Y neuroblastoma cells, comparing the effects with the non-tumoral cell line MCF10A [ 107 ]. The experimental results showed that the highest apoptosis rate was found for HTyr-treated neuroblastoma cells, while the absence of the apoptotic process induction was highlighted for the normal cell line.…”
Section: Pharmacokinetics Of Htyr and Olementioning
confidence: 89%